Penentuan Terbinafine Hidroklorida dalam Kosmetik Sediaan Pemutih Secara Kromatografi Cair Kinerja Tingg - Putri Fatmawati; Mubarokah Nuriaini Dewi; Wigayanti Wigayanti; Rinette Visca; Latirah Latirah; Joko Sulistiyo (Fakultas Teknik, 2022)
Terbinafine hydrochloride is a synthetic allylamine drug with a broad spectrum of antifungal properties. The purpose of this study was to identify terbinafine hydrochloride in whitening cosmetic products using High Performance Liquid Chromatography (HPLC). The first stage starts with dissolving cosmetic samples (A, B, C) and blanks, diluted with 25 ml of methanol. Then the solution was vortexed for 2 and centrifuged for 10 minutes at 4000 rpm. The supernatant layer formed was filtered through a 0.45 m membrane filter. Then the filtrate obtained was tested by the HPLC method. Based on the results of the system suitability test of the sample and blank, the concentration was 16????????/ml, the average retention time was 8.934 minutes and the average area was 2163340. The standard deviation of the relative retention time was 0.3098% and the area was 0.0721%. The follow-up factor and theoretical plate obtained automatically from the HPLC tool obtained an average follow-up factor value of 0.9515 and an average theoretical plate value of 217.7531. The results of the HPLC system suitability test and the terbinafine hydrochloride blank were identical, but the retention time was different, obtained from each different sample. All cosmetic samples contained Terbinafine hydrochloride as they did not meet the requirements. Regulation of the Minister of Health of the Republic of Indonesia Number 3 of 2021.